Canva and Screencast-O-Matic Workshop for Classroom Purpose: A Community Service for Madrasah Ibtidaiyah Teachers - Homsini Maolida, Elis; Salsabila, Vina Aini (AJAD : Jurnal Pengabdian kepada Masyarakat, 2021)
The pandemic has brought a lot of changes in education, as an example, distance learning has been used to facilitate young learners to learn and at the same time protect them from the spread of the Covid 19 virus. Distance learning has required teachers to be more creative in teaching so the learners can comprehend the teachers’ explanations. Workshop Canva and Screencast-O-Matic were conducted as a community service to help teachers provide more creative and interactive teaching using digital applications as learning media. It involved Madrasah Ibtidaiyah teachers in Bandung Barat. In presenting the community service process and result, descriptive qualitative was used to look at the process and interpret the result. As a result of workshop, the teachers were able to design teaching presentation by using Canva and make teaching recording. The teachers also admitted that the workshop helped them improve their digital literacy and their teaching creativity.